Umbilical cord blood banking in the worldwide hematopoietic stem cell transplantation system: perspectives for Ukraine - Kalynychenko, T.O. (Experimental Oncology, 2017)
Significant progress in the promotion of procedural technologies associated with the transplantation of hematopoietic stem cells caused a rapid increase in activity. The exchange of hematopoietic stem cells for unrelated donor transplantations is now much easier due to the relevant international professional structures and organizations established to support cooperation and standard setting, as well as rules for the functioning of both national donor registries and cord blood banks. These processes are increasing every year and are contributing to the outpacing rates of development in this area. Products within their country should be regulated by the competent government authorities. This study analyzes the work of international and national levels of support for transplantation activity in the field of unrelated hematopoietic stem cell transplantation, the standardization order of technologies, as well as data that justify the need to create a network of donated umbilical cord blood banks in Ukraine as a factor in the development of allogeneic transplantation. This will promote the accessibility of international standards for the treatment of serious diseases for Ukrainian citizens.